ANALISIS PERKEMBANGAN NILAI AGAMA DAN MORAL ANAK USIA DINI DENGAN IBADAH SHOLAT DI TPQ SAYYIDINA UMAR - muzaqi, ahmad imam; Yahya (Hamka Ilmu Pendidikan Islam, 2024)
Children are born in a state of nature or purity, children have the potential to become religious and moral humans. The development of religiosity and morality of early childhood is considered very important to discuss, therefore researchers want to conduct research on matters related to these aspects. The purpose of this study is to improve the religious and moral values of early childhood through prayer. The method in this study uses qualitative descriptive. The subjects were 6 children, namely 3 girls and 3 boys. The data collection instrument used qualitative descriptive. The research technique used observation, interview and relevant documentation techniques. From the results of the research that has been conducted, the instillation of religious and moral values  in early childhood through the habit of praying dhuha at TPQ Sayyidina Umar has an impact on the formation of children's character which can be seen from changes in children's behavior, namely: (1) children have a sense of gratitude, (2) children have good morals, and (3) children are more disciplined with time.